Implementasi Metode Analytic Hierarchy Process untuk Penentuan Prioritas Kategori Berita (Studi Kasus: LYT Media) - Khusnul Aidil Santosa; Edy Santoso; Satrio Hadi Wijoyo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
An online media company in the field of entertainment and creative industries has many categories of articles that are presented to readers, this will lead to excess material articles to be prepared by the authors. Effectiveness in the event of a news must be for the company there is a fairly. The editor-in-chief is responsible for the articles presented in the media. Obviously the company already has a category of articles presented through the criteria of entertainment and creative industries. The choice of articles is expected to maximize the visitors who read the pages of the website, so the company will benefit from the traffic that much as well. Analytic Hierarchy Process is one of the decision making methods that can provide suggestions to make category decisions from the required criteria. Hierarchical Process Hierarchy Process is a hierarchy with input of human assemblies. The Analytic Hierarchy Process procession is the use of pairwise comparison matrices to compare the relative weights between criteria and alternatives. A criterion will be compared with other criteria in terms of importance to the goal. In this research have accuration result 65,625%. The result of the process Analytic Hierarchy Process can be an efficient and effective solution in the decision categories of articles to be presented.